Olanzapine-induced thrombocytopenia in association with idiopathic thrombocytopenic purpura - Bachmann, Silke; Schröder, Johannes; Pantel, Johannes; Mundt, Christoph; Zorn, Markus; Witzens-Harig, Mathias; Egerer, Gerlinde (The British journal of psychiatry, 2018)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0007125000151463/resource/name/firstPage-S0007125000151463a.jpg